Effect of the carbon on the electrochemical performance of rechargeable Zn-air batteries. (12th February 2023) - Peng, Chunyu; Chen, Jiankang; Jin, Mengmeng; Bi, Xiaoying; Yi, Chang; Zhang, Shiming; Xu, Xinye; Liu, Weilan; Liu, Xiang; Lai, Linfei
Abstract: Carbon materials as catalyst substrates play key roles in Zn-air batteries which not only construct abundant tri-phase interfaces for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) to take place but also enable the diffusion of reactants. Carbon corrosion is known to occur in the aqueous electrolyte which leads to catalysts dissolution, electrode flooding, and rapid performance degradation. In this study, rechargeable Zn-air batteries with MnO2 as the bifunctional catalysts and different carbon as catalyst carriers, such as carbon black, CNTs, and graphene have been assembled with their electrochemical performance systematically evaluated. The correlation between the graphitization, surface, structure properties of the carbon, and the electrochemical performance of air-electrodes has been elucidated. The electrolyte composition change during cycling and the underlying corrosion mechanism of carbon have been explored. CNTs with high crystallinity and less edge exposure is an excellent candidate over activated carbon and graphene as a catalyst carrier for metal-air batteries. Highlights: Carbon corrosion plays key roles in the overall performance of air cathodes. The corrosion of amorphous carbon as Zn-air battery cathode is faster than graphitic carbon. The etching of planar structured 2D graphene in Zn-air battery produces larger carbon fragments. CNTs with high crystallinity and less edge exposure is superior to graphene and AC as Zn-air battery electrode.